Respostas

A melhor resposta!
2013-12-09T13:03:22-02:00
2x+y=7           
x+y=-1       -1

2x+y=7
-x-y=1

2x=7
-x=1

x=8

x+y=-1
8+y=-1
y=-1-8
y=-9

b)
3x+5y=21
2x-3y=-5           -1,5

3x+5y=21
-3x+4,5y=7,5

5y=21
4,5y=7,5

9,5y=28,5
y=28,5/9,5
y=3

2x-3y=-5
2x-3.3=-5
2x-9=-5
2x=-5+9
2x=4
x=4/2
x=2






1 5 1
2013-12-09T13:10:05-02:00
A)  \left \{ {{2x+y=7} \atop {x+y=-1 *(-2)}} \right. 
 \left \{ {{2x+y=7} \atop {-2x-2y=2}} \right.   , somando... y=-9

2x+y=7
2x-9=7
2x=16
x=8

B)  \left \{ {{3x+5y = 21} \atop {2x -3y = -5}} \right. 
 \left \{ {{x+5y = 21 (*2)} \atop {2x -3y = -5 *(-3)}} \right. 
 \left \{ {{6x+10y=42} \atop {-6x+9y=15}} \right. 
somando, 19y=57
y=57/19
y=3

3x+5y=21
3x+5*3=21
3x+15=21
3x=21-15
3x=6
x=6/3   x=2